Parotid Gland Rupture in a Holstein-Friesian Cow - Sharma, Rohit K.; Mishra, Saloni; Kumar, Pawan; Das, Jagdish; Bishnoi, Anil K. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
In India, ruminants, especially cattle and buffaloes, are domesticated for milk purposes; however, some leather industries and slaughterhouses also produce different livestock products from the same animals. Trauma to the salivary gland directly influences milk production of animals either because of indigestion or dehydration. The common salivary gland affections in ruminants are salivary fistula, sialolith, ectasia of the parotid duct, and sialoceles (Misk and Nigam, 1984; Misk et al., 1991; Semieka, 2002; Sagar et al., 2010). In ruminants, there are 3-paired salivary glands, viz., the parotid, mandibular, and sublingual and trauma to salivary gland infrequently occurs in cattle, may cause a wound with salivary secretions and this leakage of saliva into the surrounding tissue along with its local tissue reaction may lead to the development of a circumscribed soft swelling in the region (Singh et al. 2020). Quakes can quickly treat many clinical problems under field conditions, but trauma to the salivary gland requires special attention, and improper management of such situations leads to the life-threatening condition of the animal. Since cauterization of the gland is an easy, economical, and feasible approach under field conditions, the present case was planned for medicinal attempt rather than surgical intervention.